The Siwalik Molasse: A Sedimentary Record of Orogeny - Raynolds, R.G. H.; Johnson, G.D.; Johnson, N.M.; Opdyke, N.D. (Journal of Himalayan Earth Sciences, 1980)
The Siwalik molasse basin lies on the southern margin of the Himalayan orogenic belt. Continuously exposed from the Sulaiman Range in western Pakistan to Assam in the eastern India, the Siwalilk sediments consist of over 7000 meters of fluvial sediments ranging in age from late Miocene to Pleistocene. The continuation of the mountain building activity which first uplifted the source area to the north, is now responsible for the deformation and hence exposure of these sediments. This deformation characteristically diminishes in intensity southwards from a boundary thrust fault to the undisturbed Indo-Pakistan shield. The Siwalik sediments have been extensively studied initially because of their excellent record of late Tertiary mammalian evolution, and more recently, because of their record of source area unroofing and changing sedimentary environments.